Malaria parasite survival depends on conserved binding peptides’ critical biological functions (2016)
Biochemical, structural and single amino acid level analysis of 49 Plasmodium falciparum protein regions (13 sporozoite and 36 merozoite proteins) has highlighted the functional role of each conserved high activity binding peptide (cHABP) in cell host-microbe interaction, involving biological functions such as gliding motility, traversal activity, binding invasion, reproduction, nutrient ion transport and the development of severe malaria. Each protein's key function in the malaria parasite's asexual lifecycle (pre-erythrocyte and erythro-cyte) is described in terms of cHABPs; their sequences were located in elegant work published by other groups regarding critical binding regions implicated in malarial parasite invasion. Such cHABPs represent the starting point for developing a logical and rational methodology for selecting an appropriate mixture of modified cHABPs to be used in a completely effective, synthetic antimalarial vaccine. Such methodology could be used for developing vaccines against diseases scourging humanity. © 2016, Caister Academic Press. All rights reserved.